The Civil War : A Concise History - Masur, Louis P. (New York Oxford University Press, 2011)
War in America and its aftermath as viewed from a British perspective.
Include Index
The full name of the author of this books is William Alan Barker.
Keywords: United States -- American Civil War (1861-1865) -- United States -- History -- 1849-1877